Simultaneous profiling of classic and 11-oxygenated androgens via a novel derivatization method coupled with HPLC-MS/MS: A game-changer for endocrine disorders - Xianhua Zhang; Huiyu Xu; Yue Sun; Xin Xiong; Lingling Liu; Li Yang; Libo Zhao; Xiaona Li; Rong Li; Rongsheng Zhao (Talanta Open)
The accumulation of classic or 11-oxygenated androgens is a hallmark of polycystic ovary syndrome (PCOS). Traditional electrochemiluminescence immunoassays (ECLIA) are limited in their ability to measure a broad spectrum of androgens and may suffer from potential cross-reactivity, leading to inaccurate results. In this study, we developed a highly sensitive HPLC-MS/MS method for the simultaneous determination of nine androgens, including four classic and five 11-oxygenated androgens in human serum. Magnetic solid-phase extraction (MSPE) using magnetic graphene oxide nanoparticles followed by in-situ derivatization further improved the detection efficiency. A novel quaternary ammonium aminooxy (QAO) reagent was employed as the derivatization agent, featuring a permanently charged MS-tag and an aminooxy group that reacts with steroid ketone groups. This derivatization significantly enhanced MS sensitivity compared to traditional derivatization agents. The linear ranges for different targets were set based on clinical use and the lower limit of quantification (LLOQ) of the target androgens ranged from 0.005 to 1 ng/mL. The calibration curves exhibited excellent linear correlation (r ≥ 0.99) across the validated ranges for all the analytes. The intra- and inter-run precision was below 9.8 % and 9.7 % for the lower limit of quantification (LLOQ), and 7.5 % and 6.9 % for quality controls (QCs). Intra- and inter-day relative errors for LLOQ ranged from -8.2 % to 10.7 %, and from -7.4 % to 13.8 % for QCs. Extraction recoveries varied from 41.8 % to 80.2 %. The method was applied to 107 clinical samples, demonstrating it as a fast, sensitive and accurate method for androgens’ quantification. By offering the ability to detect and quantify a broader range of androgens, including those not measurable by ECLIA, and avoiding potential cross-reactions. This method provides a superior analytical tool for the diagnosis and management of PCOS in clinical settings.